Inhibition of Tyrosinase Activity on Dopamine Hydrochloride by Thiol Compounds - Sariri, R.; Mahmoodian, Jafar; Khaje, Khosro; Hasan Sajedi, Reza (Asian Journal of Chemistry, 2010)
This paper reports inhibits of tyrosinase activity by two thiol compounds, thioglycolic acid and 2-mercapto ethanol, using dopamine hydrochloride as substrate. Both of these ––SH containing compounds inhibited tyrosinase activity in a noncompetitive way, with Km values of 0.4050 and 0.2823 for thioglycolic acid and 2-mercaptoethanol, respectively. Other kinetic constants, Vmax, Kcat, Ki were also obtained in each case.